REV7 directs DNA repair pathway choice - Clairmont, Connor S.; D’Andrea, Alan D. (Trends in cell biology, 2021)
REV7 is a small multifunctional protein that participates in multiple DNA repair pathways, most notably translesion DNA synthesis and double-strand break (DSB) repair. While the role of REV7 in translesion synthesis has been known for several decades, its function in DSB repair is a recent discovery. Investigations into the DSB repair function of REV7 have led to the discovery of a new DNA repair complex known as Shieldin. Recent studies have also highlighted the importance of REV7’s HORMA domain, an ancient structural motif, in REV7 function and have identified the HORMA regulators, TRIP13 and p31, as novel DNA repair factors. In this review, we discuss these recent findings and their implications for repair pathway choice, at both DSBs and replication forks. We suggest that REV7, in particular the activation state of its HORMA domain, can act as a critical determinant of mutagenic versus error-free repair in multiple contexts. REV7 is a critical component of multiple complexes including well-characterized DNA repair complexes: DNA polymerase ζ and Shieldin, and other poorly understood protein complexes.REV7 is a HORMA family protein, characterized by a distinctive tertiary structure and an associated regulatory mechanism, where activity is controlled by stable conformational changes.The TRIP13 ATPase and p31 regulatory subunit remodel REV7 to the inactive HORMA conformation, inhibiting both polymerase ζ-mediated DNA synthesis and the activity of the Shieldin complex in promoting non-homologous end joining repair.REV7 plays a similar role in both Shieldin and polymerase ζ by connecting the upstream recruitment modules and downstream effector modules when REV7 is in its closed, active conformation.In both Shieldin and polymerase ζ, REV7 promotes the choice of a potentially mutagenic DNA repair pathway over higher fidelity alternatives. We propose that REV7 activity may be a powerful mechanism for a cell to fine-tune the amount of mutagenesis it is willing to tolerate.